FORMATION OF MINORITY STUDENT IDENTITY AND SCHOOL LEVEL EDUCATIONAL POLICY RESPONSE - Sulanam, Sulanam; Shodiq, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article examines how minority students form and assert their identities in school's public spaces, particularly in interactions with majority groups. This qualitative research uses interviews and documentation studies, focusing on several minority students in schools in East Java. The research results show that the identity of minority students is formed through religious expressions, which include verbal expressions, attitudes of prayer, and greetings on holidays. These three expressions function as a means for minorities to assert their identity among the majority. This research concludes that identity formation depends on significant religious expressions and small actions carried out repeatedly. Therefore, schools need to provide equitable social spaces for minority students, with policies supporting equality and respecting differences in school social life.